Tindak Tutur Dokter dan Pasien di Klinik Pratama Haji Medan-Pancing - Maya Sentia Anjelika Tampubolon; Cornelia Aginta Sembiring; Melisa Patrisia Manurung; Yanti Masryana Sianturi; Jonathan Brando Saragi; Tio Nardo Gulo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the application of speech acts in communication between doctors and patients at the Pratama Haji Medan-Pancing Clinic, focusing on the use of various types of speech acts, such as expressive, representative, directive, and commissive in medical interactions. Speech acts are understood as the smallest unit of speech activity that has a specific function, and in the medical context, this includes providing information, instructions, as well as expressions of empathy and emotional support. According to the findings from observations and interviews, effective communication between doctors and patients plays a crucial role in building trust and increasing patient satisfaction with healthcare services. According to the findings from observations and interviews, effective communication between doctors and patients plays a crucial role in building trust and increasing patient satisfaction with healthcare services. The use of appropriate speech acts, such as giving instructions on healthy lifestyles, showing empathy, and expressing care and support, plays a major role in reducing patient anxiety and improving social-emotional relationships in the hospital environment. Politeness in communication is a key element in improving the quality of health services. Therefore, the development of communication skills for medical personnel is essential to create a better experience for patients and be responsive to their needs.